A comparison of women’s expectations of labour and birth with the experiences in primiparas and multiparas with normal vaginal delivery - Pirdil, Manijeh; Pirdel, Leila (Journal of Kathmandu Medical College, 2016)
Background: Maternal childbirth expectations play an important role in determining a woman’s response to her childbirth experience. Women need to be helped to develop realistic and positive expectations and identify the factors that influence these expectations. Objective: The aim of this study was to compare woman’s expectations and experiences of childbirth. Methods: This descriptive-comparative study was carried out in Tabriz Alzahra Hospital from 2006 to 2007. For this purpose, a total of 600 primiparas and multiparas women who were candidates for vaginal delivery, were randomly selected and interviewed. The data were collected by questionnaire. Results: Comparison of the means of mothers expectation and experience of labor and birth between the two groups demonstrated a statistically significant difference (p<0.05). The findings indicated a number of differences exist between primiparas and multiparas women in relation to expectations and experiences of birth when compare two groups. The majority of women had negative expectations and experiences of childbirth. Conclusion: The evaluation and understanding of birth expectations and experiences as positive and negative is priority of maternity system. Antenatal educators need to ensure that pregnant women are appropriately prepared for what might actually happen to limit this expectation-experience gap. Health-care providers should improve the quality of antenatal care which can change negative childbirth expectations and experiences of women Journal of Kathmandu Medical College, Vol. 4(1) 2015, 16-25